Customer Satisfaction of E-Banking Services in Nepalese Commercial Banks: Evidence from Pokhara University Students - Bhattarai, Bal Ram; Karmacharya, Anujina (Journal of Business and Management, 2025)
Background:  E-banking has revolutionized the banking sector globally, and this is also the case in Nepal, where digital solutions are gradually replacing or augmenting traditional banking practices. Notwithstanding these advancements, it remains imperative to assess the perception of e-banking services among important customer segments, especially students, who constitute a technologically astute portion of the population as well as the future labor force.Objective: This study examines the relationship between customer satisfaction with the e-banking services of Nepalese commercial banks with evidence from students of Pokhara University, Pokhara, Nepal.Methods: This is a descriptive questionnaire survey of a cross-sectional research design for Pokhara University students (both Bachelor's and Master's levels). 400 questionnaires (200 online and 200 printed) were distributed after constructing a five-point Likert scale, along with a pilot test of 15 responses, which were administered to university students using a convenience sampling method. However, only 204 usable responses were found for drawing the result. Questionnaire development and hypothesis tests are primarily based on the SERVQUAL model.Results: The findings reveal a significant positive relationship between customer satisfaction and aspects of service quality, particularly assurance, tangibility, responsiveness, and reliability. Despite a positive correlation, empathy has a less significant impact on customer satisfaction. Results further indicate that these four factors significantly contribute to customer satisfaction, while empathy plays a lesser role.Conclusion: This study concludes that reliability, responsiveness, assurance, and tangibles dimensions of service quality positively drive customer satisfaction with e-banking services of commercial banks among university students. However, a detailed study covering various sectors is desirable for the generalizability of the study findings.